Craft in America [videorecording (DVD)] - Noble, Nigel; Seeger, Dan; Birmingham, Hilary; Oglesby, Randy (Distributed by PBS Home Video, 2007)
"Craft in America is an exploration into the hearts and minds of artisans devoted to a diverse array of mediums -- from furniture making and basket weaving to pottery and metalsmithing. Each episode reveals that craft has earned itself a place within the realm of fine art"--Container.